BCA2/Rabring7 Targets HIV-1 Gag for Lysosomal Degradation in a Tetherin-Independent Manner - Nityanandam, Ramya (Public Library of Science, 2014)
BCA2 (Rabring7, RNF115 or ZNF364) is a RING-finger E3 ubiquitin ligase that was identified as a co-factor in the restriction imposed by tetherin/BST2 on HIV-1. Contrary to the current model, in which BCA2 lacks antiviral activity in the absence of tetherin, we found that BCA2 possesses tetherin-independent antiviral activity. Here we show that the N-terminus of BCA2 physically interacts with the Matrix region of HIV-1 and other retroviral Gag proteins and promotes their ubiquitination, redistribution to endo-lysosomal compartments and, ultimately, lysosomal degradation. The targeted depletion of BCA2 in tetherin-expressing and tetherin-deficient cells results in a significant increase in virus release and replication, indicating that endogenous BCA2 possesses antiviral activity. Therefore, these results indicate that BCA2 functions as an antiviral factor that targets HIV-1 Gag for degradation, impairing virus assembly and release.